For a Rebellious Early Modern Europe. Notes on the Margins of the Most Recent Works by Luise Schorn-Schütte - Ptaszyński, Maciej (Odrodzenie i Reformacja w Polsce, 2018)
The early modern age dubbed itself a “new” era, distinguishing itself, in Christoph Cellarius’ description, from the middle age and antiquity. This novitas was marked by cultural, social, religious, and political changes, not always positively evaluated by their contemporaries. With the onset of mental changes at the turn of the nineteenth and twentieth centuries, the early modern era became a historical period preceding and preparing the coming of modernity.